2018
DOI: 10.1080/09593330.2018.1428227
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamethoxazole removal in membrane-photocatalytic reactor system – experimentation and modelling

Abstract: In this study, the efficacy of membrane-photocatalytic reactor (MPR) in sulfamethoxazole (SMX) removal was explored at a fixed initial SMX concentration, i.e. 100 mg/L. A supported catalyst, i.e. TiO on granular activated carbon (GAC-TiO), was used for MPR experiments. The SMX removal efficiency of the MPR was investigated under a range of hydraulic retention time (i.e. HRT from 51 to 152.5 min) and TiO catalyst dosage (55-50 mg/L). A maximum SMX removal efficiency of 83.6% was observed under 220 mg/L catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Comparing the experimental data with the prediction results, it is found that the model has a good prediction effect [168]. In order to study the effects of hydraulic retention time and photocatalyst dosage on the degradation effect of sulfamethoxazole in membrane photocatalytic reactor systems, Asha et al established a multiple nonlinear regression model based on experimental data, which effectively predicted the optimal hydraulic residence time and photocatalyst dosage in membrane photocatalytic reactor systems [169]. For parameters such as irradiation uniformity and reactor structure that are not easy to quantify, software simulation is a valuable tool to optimize.…”
Section: Optimal Adjustment Of Parametersmentioning
confidence: 99%
“…Comparing the experimental data with the prediction results, it is found that the model has a good prediction effect [168]. In order to study the effects of hydraulic retention time and photocatalyst dosage on the degradation effect of sulfamethoxazole in membrane photocatalytic reactor systems, Asha et al established a multiple nonlinear regression model based on experimental data, which effectively predicted the optimal hydraulic residence time and photocatalyst dosage in membrane photocatalytic reactor systems [169]. For parameters such as irradiation uniformity and reactor structure that are not easy to quantify, software simulation is a valuable tool to optimize.…”
Section: Optimal Adjustment Of Parametersmentioning
confidence: 99%
“…SMX residues in surface and ground waters can be harmful to both fauna and ora, making it necessary to nd an effective and economical technology for its removal as the current water treatment system is not equipped to handle this problem. 7,8 Various methods have been employed to eliminate SMX from water, including ltration, 9 membrane ltration, 10 adsorption, 11 electrochemical catalysis, 12 sonolysis, 13 coagulation, 14 biodegradation, 15 photocatalysis, 16 ozonation, 17 and advanced oxidation processes (AOPs). 18,19 Recently, AOPs such as photocatalysis and sonocatalysis have been receiving much attention owing to their advantage of being able to convert organic water pollutants to low molecular weight substances and the fact that they have proven to be more efficient in eliminating pollutants due to their synergistic effect.…”
Section: Introductionmentioning
confidence: 99%